First case of Propionibacterium acnes urinary tract infection in a dog. Issue 1 (December 2015) - Harada, Kazuki; Shimizu, Takae; Tsuka, Takeshi; Imagawa, Tomohiro; Takeuchi, Takashi
Abstract Background Propionibacterium acnes has been rarely isolated as a commensal from dogs, but there is little evidence of pathogenicity. Urinary tract infections are common in dogs and are typically caused by various commensal bacteria. Here we present the first case report of a urinary tract infection caused byP. acnes . Case presentation A 6-year-old female Japanese Shiba Inu was hospitalized for polyuria, polydipsia, and severe hematuria. At admission, blood tests revealed leukocytosis, slight anemia, decreased albumin, and slightly elevated blood urea nitrogen. Computerized tomography showed gas accumulation on the inner side of the bladder wall. Urinalysis revealed proteinuria and bilirubinuria without glycosuria. The urine sediment contained large numbers of erythrocytes and leukocytes. Additionally, rod-shaped bacteria were detected by Diff-Quik staining. Enrofloxacin and metronidazole were administered empirically; however, the renal function declined sharply and the patient died 2 days later. Bacteriological examination revealed that the causative agent wasPropionibacterium acnes, which was identified as sequence type 53 via multilocus sequence typing. This isolate showed high susceptibility to ampicillin, amoxicillin/clavulanic acid, cefoxitin, imipenem, clindamycin, tetracycline, chloramphenicol, and enrofloxacin, but was resistant to metronidazole. Conclusion To the best of our knowledge, this is the first case report of a dog with urinary tract infection caused byP. acnes .